Creep and mechanical behavior after sustained loading of red mud-slag based geopolymer concrete at early-age - Xiaolei Zhang; Yongbao Wang; Jianglong Han; Xu Li (Case Studies in Construction Materials)
To investigate the effects of stress levels, silica fume contents, fiber types, and fiber contents on the drying shrinkage, creep, and mechanical properties of early-age Red mud-Slag based GeoPolymer Concrete (RS-GPC), a comprehensive series of experiments, including compressive strength, drying shrinkage, creep were conducted. Based on experimental results and existing models, drying shrinkage and creep prediction models, as well as constitutive relationship models before and after creep, were developed. Respectively, the results revealed that the 7-day cube compressive strength, 28-day drying shrinkage, and creep coefficient of RS-GPC ranged from 29.36 to 57.03 MPa, 330–500 με, and 1.71–2.03. The incorporation of silica fume significantly reduced drying shrinkage but notably weakened compressive strength and creep. Conversely, optimal content of steel fiber and basalt fiber enhanced these properties significantly. After creep, the elastic modulus of RS-GPC increased, whereas peak and ultimate strain decreased. For most test groups, axial compressive strength after creep decreased, with the exception of those incorporating silica fume. The proposed stress-strain curve equations demonstrated good agreement with experiment, underscoring the impact of sustained loading on constitutive relationships. In conclusion, silica fume and fibers exhibit dual effects on the mechanical and shrinkage properties of RS-GPC. Moreover, creep significantly reduces axial compressive strength. It is necessary to consider mechanical properties after creep in the structural design of RS-GPC members subjected to sustained loading.